2004
DOI: 10.1111/j.1743-6109.04043.x
|View full text |Cite
|
Sign up to set email alerts
|

Vardenafil Improves Erectile Function in Men with Erectile Dysfunction Irrespective of Disease Severity and Disease Classification

Abstract: Background Vardenafil (Levitra®) is a potent and selective phosphodiesterase 5 (PDE5) inhibitor used in the management of erectile dysfunction (ED). This retrospective subgroup analysis assessed the effectiveness of vardenafil treatment in men with ED of different baseline severity and disease classification. Methods Data from two pivotal, randomized, double-blind, placebo-controlled clinical trials enrolling men from the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
4
15
0
1
Order By: Relevance
“…The present study showed that vardenafil effectively improves EF compared with placebo, consistent with the findings of other clinical studies with vardenafil [11][12][13][14][15][16][17][18][19]. For the primary efficacy variable (change in IIEF-EF domain score at week 12), the analysis showed a highly statistically significant difference in favor of vardenafil (P < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that vardenafil effectively improves EF compared with placebo, consistent with the findings of other clinical studies with vardenafil [11][12][13][14][15][16][17][18][19]. For the primary efficacy variable (change in IIEF-EF domain score at week 12), the analysis showed a highly statistically significant difference in favor of vardenafil (P < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…The observed improvement in erectile function was reflected in the significant increase in men who returned to normal erectile function (IIEF‐EF score ≥26), compared with men who received placebo. The improvement in erectile function was consistent with that seen in previous trials, in which vardenafil demonstrated efficacy in a broad population of men with ED of varying etiology and severity, including men who had undergone prostatectomy and those with diabetes, who are generally considered to be difficult to treat [17–21].…”
Section: Discussionsupporting
confidence: 84%
“…Vardenafil is a potent selective PDE-5 inhibitor that has been shown to be highly efficacious in men with erectile dysfunction, irrespective of severity or disease classification (organic, psychogenic, or mixed) (11) or underlying etiology (12). The drug is well tolerated and is associated with a rapid and reliable treatment response.…”
Section: Discussionmentioning
confidence: 99%